Common Health Concerns in African Immigrants in the Us- Implications for the Family Physician - Okudo, Jerome C; Ross, Michael W (International Journal of Medical and Health Sciences Research, 2016)
African immigrants in the US encounter many issues on arrival to the US over time. The healthy immigrant effect (HIE) is a phenomenon that should be explored as many African immigrants lose their HIE on adoption of the ‘American lifestyle’. Family medicine practices in the US encounter a significant African immigrant population from different African countries, which is an underserved population. Highlighting their health issues will enable the family physician to become aware of their unique needs and manage these patients in their clinical practices. African immigrants tend to be viewed as ‘all from Africa’ when indeed Africa is a continent with 54 countries. Some of these unique health problems, though suffered by Americans may be differently manifested and therefore may require special management. Africans continue to migrate to the US and family medicine practitioners that are the first point of contact need to be educated to holistically manage them. Barriers to seeking health care and issues of physician patient relationship are important areas that also need to be explored in this special population.